The Influence of Leadership Style, Employee Engagement, and Work Environment on Service Quality: A Systematic Literature Review - Sabarini, Nur Endah; Supardi, Supardi (Dinasti Publisher, 2026)
This study aims to examine the influence of leadership style, employee engagement, and work environment on service quality through a Systematic Literature Review (SLR) approach. Data were collected from scientific articles systematically selected using the PRISMA procedure from Scopus-indexed databases and reputable international journals (2018–2024), resulting in 20 high-quality articles. Findings reveal that transformational leadership style demonstrates the strongest influence on service quality (r = 0.58), followed by servant leadership (r = 0.52). Employee engagement acts as a significant partial mediator in the relationship between leadership and service quality, with an indirect effect contribution of 35–60%. The work environment significantly contributes to service quality (r = 0.52), with the socio-psychological dimension exerting a stronger influence (60%) than the physical dimension (40%). A strong synergistic effect exists among the three variables, where integrated optimization yields a 35–45% improvement in service quality. This study provides a theoretical contribution in the form of a holistic conceptual framework for comprehensively understanding the determinants of service quality.